Intervention the use of American military force in the post-Cold War world - Haass, Richard (Washington, DC Carnegie Endowment for International Peace, 1994)
contrary to the expectations of some and the hopes of many, the demise of the Soviet Union and the end of the Cold War did not bring about an era of peace and stability. Rather, conflict between and within states is commonplace, and threaten to become more violent and dangerous with the spread of unconventional arms and the means to deliver them. Important, even vital, U.S. interests could be jeopardized in such a
1
Keywords: World politics -- 1989-; United States -- Military policy; United States -- Military relations